Modeling transition paths towards decentralized regional energy autonomy: the role of legislation, technology adoption, and resource availability - Binder, Claudia R.; Knoeri, Christof; Hecher, Maria (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Decentralized energy systems are increasingly seen as a key factor for a transition towards a low-carbon, renewable energy based society. Within the transition process, regional demand and supply of renewable energy carriers have to be aligned, while considering the environmental conditions of the region. This paper focuses on the energy demand from buildings, which makes up 35 % of the total energy demand. It presents an approach for aligning the regional supply potential of renewable energy carriers with the dynamics of regional energy demand from buildings. The approach consists of two components. First, a dynamic model simulates regional energy demand from buildings taking into consideration envelope renovation, legislative standards, and adoption of heating technologies. Second, the regional supply is estimated based on the technical maximum possible, taking into consideration competing uses and spatial limitations. We show a first application in the case of the energy region Weiz-Gleisdorf, Austria, which aims to achieve CO2 neutrality and energy self-sufficiency by the year 2050. Our results show that in the year 2050 (i) energy demand from buildings will decrease by 40–55 %, depending on envelope renovation rates and legislative standards; (ii) demand for the different renewable energy carriers will be determined by the choice of heating technology; (iii) the demand for wood could be met from regional forest resources, as long as there are no additional demands for other purposes; (iv) the demand for biomass for district heating would require 5–10 % of the agricultural area to be used for the production of energy plants rather than food; and (v) in contrast to other forms of energy, the demand for electricity will remain constant or increase slightly over time. This demand could only be regionally met if significant areas of façades or gardens are used for photovoltaic electricity production in addition to roofs. Overall we identified several issues related to spatial planning and a need for further research regarding the transition towards decentralized energy systems. First, if biomass for central district heating systems is to come from regional production, areas should be allocated for cultivating energy crops used specifically to produce fuel. Second, if wood is used for district heating purposes, the extent to which the import of wood from neighboring regions would be a useful ecological solution must be evaluated; this would involve extending regional energy planning beyond the typical jurisdictional boundaries while considering ecological issues.
Keywords: Regional energy demand; Energy supply; Spatial limitations; Renewables; Energy transition